Upcycling of biomass waste into photothermal superhydrophobic coating for efficient anti-icing and deicing. (May 2022) - Wang, B.; Yu, P.; Yang, Q.; Jing, Z.; Wang, W.; Li, P.; Tong, X.; Lin, F.; Wang, D.; Lio, G.E.; Caputo, R.; Ávalos-Ovando, O.; et al.
Abstract: Superhydrophobic surfaces coupling with photothermal effect, as a passive solution independent of external energy input, have shown promising perspectives for anti-icing and deicing. However, most hydrophobic photothermal materials are costly and require complicated fabrication processes, which limit their development in large-scale applications. Here, a facile method is proposed to fabricate superhydrophobic photothermal anti-icing coating using commercially available biochar (BC) and low-cost titanium nitride (TiN) nanoparticles. The coating displays superior photothermal conversion and anti-icing performance, benefiting from the micro-nano hierarchical structure's light trapping effect and high surface roughness. Meanwhile, the coating shows an extra-long anti-icing time of ∼831s for water droplets, which is ∼17 times longer than pure BC coating. The covering frost and ice can be melted into droplets under the illumination of sunlight and roll off rapidly, leaving a dry surface. The superhydrophobic photothermal coating may promote the development of anti-icing and deicing surfaces in outdoor applications. Graphical abstract: Image 1 Highlights: Commercially available biochar (BC) is firstly utilized to fabricate superhydrophobic photothermal anti-icing coating. After adding 20 wt% fluorinated TiN, the surface exhibits a large water CA up to 156° and a RA as low as 5°. The coating shows an extra-long anti-icing time for water droplets, which is ∼17 times longer than pure BC coating. The method is easy to integrate with various surfaces and enables rapid ice melting through photothermal effects.